Ugh, that's ugly! - Guibert, Grace (Chicago World Book Inc, 2018)
Describes some of the strangest, slimiest, and ugliest looking animals, including the blobfish, wrinkle-faced bat, and elephant seal. Includes large photographs and relevant information about each animal presented
Kids Age 5-11